Meta-Analysis the Impact of Social Restriction during COVID-19 Pandemic on Blood Glucose Control in Type 1 Diabetes Mellitus Patients - Yeocelin Mega Pratiwi; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Epidemiology and Public Health, 2022)
Background: The COVID-19 lockdown has an impact on the daily lives of people with type 1 diabetes, including restrictions on physical activity, changes in diet, difficulty contacting health care providers and concerns about drug supplies. The purpose of this study was to analyze the impact of the COVID-19 lockdown on blood sugar control in type 1 diabetes mellitus patients.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The PICO model used is Population= type 1 diabetes mellitus patients. Intervention = COVID-19 lockdown. Comparison = before the COVID-19 lockdown. Outcome = HbA1c. The article search process was carried out between 2019 and 2022 using online databases from PubMed, Springer Link and Google Scholar. The keywords used in the article search were “Quarantine” OR “Quarantines” OR “Stay at Home Orders” OR “Health Lockdowns” OR “Self-Quarantine” OR “Self-Quarantine” AND “Diabetes Mellitus” OR “Diabetes Insipidus” OR “Diabetic” OR “Glucose Intolerance” AND “Glycemic Control” OR “Blood Glucose Control”. The inclusion criteria used in this study were full paper articles with cohort studies, using English or Indonesian, the intervention given was COVID-19 lockdown, and the outcome was blood glucose level (HbA1C) in diabetes mellitus patients.The analysis was performed using RevMan 5.3 software.Results: A total of 11 articles reviewed in the meta-analysis showed that the impact of the COVID-19 lockdown decreased HbA1c levels by 0.23 compared to before the COVID-19 lockdown in patients with type 1 diabetes mellitus and was statistically significant (SMD= -0.23; 95% CI -0.29 to -0.18; p<0.001).Conclusion: COVID-19 lockdown reduces HbA1c levels compared to before COVID-19 lockdown in type 1 diabetes mellitus patients. Keywords: COVID-19 lockdown, type 1 diabetes mellitus, HbA1c. Correspondence:Yeocelin Mega Pratiwi. Masters Program in Public Health, Universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: yeocelinmega@gmail.com. Mobile: 082137652605.